Microcirculation Revisited - From Molecules to Clinical Practice 2016
DOI: 10.5772/64435
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Inflammation and Microcirculation in Surgery: Clinical Strategies for Improved Surgical Outcomes

Abstract: Impaired microcirculation secondary to underlying vascular endothelial dysfunction is increasingly recognized to play a central role in the pathophysiology associated with numerous postoperative complications. Noxious stimuli, including direct injury from surgical trauma and hypoxia (e.g., ischemia-reperfusion injury), trigger adrenergicinflammatory-thrombotic-immune cascades to impair the microcirculation, with consequent perfusion-related postoperative complications. The endothelium, characterized by exquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
(104 reference statements)
1
1
0
1
Order By: Relevance
“…The impairment of microcirculatory perfusion may be independent of systemic hemodynamics. 43,52,53 This was also evident in this study, which revealed only a weak correlation between MAP and De Backer score during the intraoperative period. De Backer et al reported that the microcirculatory perfusion might only deteriorate when MAP is lower than 60-65 mmHg.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The impairment of microcirculatory perfusion may be independent of systemic hemodynamics. 43,52,53 This was also evident in this study, which revealed only a weak correlation between MAP and De Backer score during the intraoperative period. De Backer et al reported that the microcirculatory perfusion might only deteriorate when MAP is lower than 60-65 mmHg.…”
Section: Discussionsupporting
confidence: 78%
“…In patients with chronic inflammation, the endothelium has been activated much earlier than the time of surgery and is associated with elevated suPAR levels. 12,43 In these individuals, graded changes in venular shear rate even for brief periods elicit progressive recruitment of both rolling and firmly adherent leukocytes. 44,45 The activated leukocytes cause oxidative and enzymatic degradation of the glycocalyx and further impair microvascular perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Як відомо із літературних джерел, саме інтраопераційний період є визначальним етапом формування ускладнень та основним етапом формування спайкового процесу [3]. В цей період важливим моментом є не лише вплив маніпуляцій у черевній порожнині, негативний вплив препаратів для наркозу, а й такий фактор, як стан мікроциркуляції, ступінь ендогенної інтоксикації та температурний гомеостаз [4][5][6].…”
unclassified